Of Persepolis and Jerusalem. Towards an evaluation of Iranian influence on the Jewish apocalyptic traditions - Silverman, Jason M. (Trinity College (Dublin, Ireland). Department of Religions and Theology, 2010)
This dissertation presents the need for a reconsideration of Iranian influence upon Jewish apocalyptic, and offers grounds upon which such study may proceed. The Prolegomena describes the history of scholarship on the question of Iranian influence and on Jewish apocalyptic and offers grounds upon which comparative research ought to be conducted. Chapter I describes the sources for Iranian religion, the issues involved in attempting a historical reconstruction, and the methodology by which one can date the various texts and ideas. Chapter II argues for the historical and sociological likelihood of Iranian-Judaean interaction by discussing the various places in which the two communities could have interacted.
Keywords: Religions and Theology, Ph.D.; Ph.D. Trinity College Dublin.